Blood elemental levels and antioxidant markers in humans with atherosclerotic disease - Lopes, Paula Alexandra (2003)
Although mortality from coronary heart disease has declined recently, atherosclerosis and related vascular diseases are still the major cause of death in the western countries. Experimental studies have demosntrated that a disturbed balance between free radical formation and antioxidant defenses can play a role in the development and progression of various diseases, namely atherosclerosis. In this study trace element levels were measured in plasma and in blood cells of subjects suffering from atherosclerotic disease. Blood activities of antioxidant enzymes, superoxide dismutase (SOD) and glutathione peroxidase (GPx) and plasma total thiols were also evaluated in these patients. Significantly decreased Se and Fe were found in the blood plasma of the atherosclerotic group. A tendency for disruption in antioxidant enzyme status was observed in these patients, but plasma total thiols were unchanged. These are preliminary results and a large atherosclerotic group is required in order to clarify the observations and to contribute for the knowledge on the molecular basis of atherosclerosis.